Anti-Cancer Assessment of a Ramie (Boehmeria nivea L. Gaud.) Leaf Extract Using Mcf-7 Cell Line and a Yeast-Based Bioassay - Asri Peni Wulandari; Annisa Abdiwijaya Qaromah; Karen Kezia Lolowang; Desi Harneti Putri Huspa; Ade Zuhrotun (Future Science, 2021)
Introduction: One strategy for molecular cancer therapy is to know the key mechanism of cytotoxic compounds that can kill cancer cells. Ramie (Boehmeria nivea L. Gaud.) leaves contain active compounds that have important effects on cancer chemoprevention. Objective: To obtain the active fraction of a Ramie leaf extract in inhibiting the proliferation of MCF-7 breast cancer cell lines and to determine the mechanism of apoptosis induction using MCF-7 and Saccharomyces cerevisiae strains 1140, 1353, and 1138. Method: Fractions were prepared using n-hexane, dichloromethane (CH2Cl2), ethyl acetate, and n-butanol as solvents. All fractions were tested qualitatively through phytochemical. The MTT-based cytotoxicity assay used MCF-7 (in vitro) to obtain the IC50 value, whereas the model system that targets the enzymatic (topoisomerase) used a yeast-based bioassay to obtain the IC12 value. Apoptotic induction of the active fraction in MCF-7 was performed using flow cytometry and qPCR (2-ΔΔCt method). Results: The phytochemical analysis indicated that the extract fraction consisted of alkaloids and steroids. The smallest IC50 value was obtained from the CH2Cl2 fraction as 3.79 g/mL, potentially act as an anticancer. A higher percentage of apoptosis than that of necrotizing cells and live cells was observed through flow cytometry. The CH2Cl2 fraction with an IC12 value < 8000 in strains 1140, 1353, and 1138 consistently showed the mechanism of apoptosis induction as topoisomerase I and II inhibitors. Also, another mechanism could be through the intrinsic pathway, indicated by the highest expression level in p53. Conclusions: The CH2Cl2 fraction of Ramie leaves can inhibits the proliferation of MCF-7 cells in the active and strong categories. The CH2Cl2 fraction induces apoptosis by increasing p53 gene expression and inhibiting topoisomerase I and II. Thus, it showed potential as an anticancer drug candidate.